Green Marketing Tools, Religiosity, Environmental Attitude And Green Purchase Behaviour Among Millenials Generation - Solekah, Nihayatu Aslamatis; Premananto, Gancar; Hartini, Sri (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2020)
The purpose of the research isto examine relationship between Green Marketing Tools (GMT), Environmental Attitudes (EA), Religiosity and Green Purchase Behavior (GPB) and test Religiosity moderates between Environmental Attitudes (EA) and Green Purchase Behavior (GPB). This study employs samples using a questionnaire instrument. The result of the collected 268 questionnaires of respondents were processed using descriptive and quantitative analysis data using SEM (Strutural Equation Model) analysis techniques with Stata 13. The resultsÂ showed that millennial generation in shaping their engagement behavior on environmental issues is influenced by environmentally friendly advertisements, attributes or labels used on a product, then perceptions of environmentally friendly brands and trust in environmentally friendly advertisements, trust in compliance or environmentally friendly labels and brands that are on the products they know.The findings of this study suggest that individual factors in the form of religious and situational factors in the form of green marketing tools in the form of eco labels, eco brands, trusts or trust in eco labels and eco brands, and environmental advertising affect green behavioral.